Revitalisasi Seni Pertunjukan Rakyat Kethoprak di Yogyakarta - Wibono, Joanes Catur (Institut Seni Indonesia Yogyakarta, 2010)
Kethoprak revitalization in Yogyakarta. This writing scrutinize kethoprak as one of the performing art varieties that develops along with the age transformation. It is because of its devotees ensure the kethoprak revitalization process to take place. The process is carried out both textually and contextually. The revitalization is not merely done by repeating the show as an action to perpetuate the tradition but also covers undertaking the efforts to improve and to renew it, in its textual as well as contextual aspects, to fulfill the existing demand. Keywords: kethoprak, revitalization, textual, contextual